Relationship between the heterogeneity of low-permeability reservoirs and the dynamic evolution of fractures under uniaxial compression conditions by CT scanning: A case study in the jiyang depression of Bohai Bay Basin, China - Li, Li; Shi, Guangyao; Zhang, Yixin; Liu, Xiangwei (Frontiers in Earth Science, 2023)
Based on an analysis of core fracture and computed tomography scanning by X-ray under uniaxial compression tests with loading and unloading, the three-dimensional evolution of fracture initiation and propagation in different heterogeneity conditions of low-permeability reservoirs was investigated in this study. Reservoir heterogeneity affects the 3D dynamic development of fractures. With an increase in the loading value, fractures in strong heterogeneity of low-permeability reservoirs followed the development sequence from shallow to deep depth in the profile. When the fracture tip reached the incompetent layer, propagation stopped. Subsequently, when the deformation continued to increase, the fracture crossed the incompetent layer and initiated a new fracture at the front end. Therefore, the across-bedding and through-going macro fractures formed in conjugate sets or Y-shaped, with roughly equal spacing. In the plane, fractures initiated along the pre-existing bedding parallel fracture and further propagated into large fractures. Consequently, they formed a net shape fracture from edge to center, with a long development period. These fractures intersected to construct a complex, interconnected, and high-fracture-density system in three dimensions. Under the same loading value, owing to uniform lithology, the formation of micro-fractures in the weak heterogeneity of low-permeability reservoirs is difficult. Further, long shear fractures were only produced in a relatively short formation period with small fracture density. In the plane, fractures stepped in an en-énchelon and terminated with horse-tailing microfractures. Moreover, strong heterogeneity of low-permeability reservoirs was more favorable in producing fractures; the fracture volume was 13.17% of the total sample volume compared to the 0.67% in that of the weak-heterogeneity reservoir under the same loading compression. Furthermore, a better fracturing effect was achieved by fracturing along the direction greater than 50° with the natural fracture, and under the condition of small differential horizontal stresses.